2005
DOI: 10.1542/peds.2005-0249
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the National Institutes of Health Consensus Definition of Bronchopulmonary Dysplasia

Abstract: The consensus BPD definition identifies a spectrum of risk for adverse pulmonary and neurodevelopmental outcomes in early infancy more accurately than other definitions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
636
4
27

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,031 publications
(688 citation statements)
references
References 45 publications
9
636
4
27
Order By: Relevance
“…BPD was determined by an oxygen reduction test at 36 weeks of postmenstrual age, and the severity was further judged using criteria adapted from the National Institute of Child Health and Human Development 30. NEC was determined by symptoms and x‐ray examination and classified according to Berman and Moss 31.…”
Section: Methodsmentioning
confidence: 99%
“…BPD was determined by an oxygen reduction test at 36 weeks of postmenstrual age, and the severity was further judged using criteria adapted from the National Institute of Child Health and Human Development 30. NEC was determined by symptoms and x‐ray examination and classified according to Berman and Moss 31.…”
Section: Methodsmentioning
confidence: 99%
“…(1-7) Many very low birth weight infants with and without a history of bronchopulmonary dysplasia (BPD) continue to have symptomatic pulmonary disease in the first years after discharge from neonatal intensive care, often manifesting as wheezing, a dependence on pulmonary medications, and episodic re-hospitalization for respiratory disease. (8)(9)(10)(11) For example, Greenough et al showed that at 12 months of age, 42% of very premature infants experienced wheezing, 36% used bronchodilators, and 17% used inhaled steroids. (2) In the NO CLD randomized clinical trial, inhaled nitric oxide (iNO) treatment increased survival without BPD at 36 weeks corrected gestational age in a group of very low birth weight infants at high risk for pulmonary morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…BPD was further classified for each baby based on the published criteria. 21 In addition, detailed information on parenteral and enteral feedings, growth, length of stay and central line days were collected. Total line days were defined as days with one central line; and if two central lines were in place on the same day, this was counted as one line day.…”
Section: Methodsmentioning
confidence: 99%
“…Severe BPD is associated with an increased risk of life-threatening respiratory infection, abnormal pulmonary function testing into late childhood, and an increased risk for neurodevelopmental sequelae compared to babies with mild or no BPD. 21 And, surgical necrotizing enterocolitis (NEC) is associated with neurodevelopmental delay. 22,23 In this study, we investigated the growth and nutritional parameters in cohorts of neonates born during the 18-month periods before and after the introduction of three EMPC for our ELBW neonates.…”
Section: Introductionmentioning
confidence: 99%